Comparative evaluation of several toric intraocular lens calculators for predicting postoperative refractive astigmatism in cataract surgery: a real-world study - Haocheng Xian; Bingzhen Li; Ziyao Xia; Chun Zhang; Xuemin Li (BMC Ophthalmology)
Abstract Background This study aims to comprehensively evaluate the predictive accuracy of six widely used toric intraocular lens (IOL) calculators in eyes undergoing cataract surgery with toric IOL implantation. Methods This retrospective study reviewed 53 eyes of 53 patients that underwent cataract extraction with toric IOL implantation using Zeiss 709 M. Six toric IOL calculators were evaluated: Barrett toric calculator (with predicted PCA, measured PCA, and TK), Kane formula (predicted PCA), and EVO 2.0 formula (predicted and measured PCA). Postoperative refractive astigmatism prediction errors were comprehensively calculated and analyzed using vector analysis. Results The mean absolute prediction error (APE) ranged from 0.56 ± 0.37 D (Barrett TK) to 0.63 ± 0.46 D (Barrett predicted PCA, PPCA). The proportions of eyes achieving APE ≤ 1.0 D were highest for Barrett TK and Kane predicted PCA (90.6%). The highest proportions of eyes achieving APE ≤ 0.25 D and ≤ 0.50 D were observed with Barrett measured PCA (18.9% and 56.6%, respectively), while the lowest with Barrett PPCA (9.4% and 50.9%, respectively). The study found no statistically significant differences in mean absolute prediction error (APE) among the six calculators (χ² = 6.88, P = 0.23) and the centroid of PE (P = 0.93). A difference in mean APE was observed between the Barrett predicted PCA and Barrett TK calculators (P = 0.02). Conclusion The study confirms the importance of considering posterior corneal astigmatism remains essential to achieving precise refractive outcomes but also underscores the need for ongoing refinement and evaluation to optimize surgical outcomes.